Penerapan Kepemimpinan Islam dan Pengaruhnya terhadap Kinerja Pengelola Ksp Syariah di Kabupaten Wajo dan Kabupaten Enrekang - Syamsuddin (Universitas Brawijaya, Indonesia, 2014)
The aims of this study are to know the implementation of Islamic leadership and employee performance, then to analyze the effect of Islamic leadership on employee performance of KSP Syariah in Wajo and Enrekang Regency. The number of samples are taken 36 people from 74 people population of employee KSP Syariah in Wajo and Enrekang Regency. Sampling technique is accidental random sampling. Data collection technique is documentation and questionnaires. Analysis of the data used descriptive and linear regression models. The results of this study indicate that the implementation of Islamic leadership is good but it is important to increase as well as employee performance. The implementation of Islamic leadership will influence toward the improvement of employee performance of KSP Syariah in Wajo and Enrekang Regency.